Modeling and administration scheduling of fractional-order pharmacokinetic systems - Herceg, Domagoj; Ntouskas, Sotiris; Sopasakis, Pantelis; Dokoumetzidis, Aris; Macheras, Panos; Sarimveis, Haralambos; Patrinos, Panagiotis (IFAC PAPERSONLINE, 2017)
Fractional-order dynamical systems were recently introduced in the field of pharmacokinetics where they proved powerful tools for modeling the absorption, disposition, distribution and excretion of drugs which are liable to anomalous diffusion, deep tissue trapping and other nonlinear phenomena. In this paper we present several ways to simulate such fractional order pharmacokinetic models and we evaluate their accuracy and complexity on a fractional order pharmacokinetic model of Amiodarone, an anti-arrhythmic drug. We then propose an optimal administration scheduling scheme and evaluate it on a population of patients. (C) 2017, IFAC (International Federation of Automatic Control) Hosting by Elsevier Ltd. All rights reserved.
Keywords: Drug administration; Fractional-order systems; Pharmacokinetics